Creating uniform fashion designs for students Vocational secondary schools (Journal of the College of Basic Education, 2022)
The current research aims to develop unified designs with distinctive privacy for students of vocational secondary schools in accordance with the specific specifications of this academic and age stage.The importance of research comes in the first chapter in that it contributes to finding the characteristic of autism and privacy in the clothing appearance of students in vocational schools through uniform costumes. It also contributes to helping fashion designers and specialized sewing factories by identifying special designs within this study stage with the possibility of developing designs. The equipment is put into practice, and it is possible that this research will serve students who are researchers in such fields in developing fashion designs for other academic and age groups.